On‐chip electromembrane extraction of acidic drugs. Issue 18 (2nd April 2019) - Roman‐Hidalgo, Cristina; Santigosa‐Murillo, Elia; Ramos‐Payán, María; Petersen, Nickolaj J.; Kutter, Jörg P.; Pedersen‐Bjergaard, Stig
Abstract: In the present work, a new supported liquid membrane (SLM) has been developed for on‐chip electromembrane extraction of acidic drugs combined with HPLC or CE, providing significantly higher stability than those reported up to date. The target analytes are five widely used non‐steroidal anti‐inflammatory drugs (NSAIDs): ibuprofen (IBU), diclofenac (DIC), naproxen (NAX), ketoprofen (KTP) and salicylic acid (SAL). Two different microchip devices were used, both consisted basically of two poly(methyl methacrylate) (PMMA) plates with individual channels for acceptor and sample solutions, respectively, and a 25 µm thick porous polypropylene membrane impregnated with the organic solvent in between. The SLM consisting of a mixture of 1‐undecanol and 2‐nitrophenyl octyl ether (NPOE) in a ratio 1:3 was found to be the most suitable liquid membrane for the extraction of these acidic drugs under dynamic conditions. It showed a long‐term stability of at least 8 hours, a low system current around 20 µA, and recoveries over 94% for the target analytes. NPOE was included in the SLM to significantly decrease the extraction current compared to pure 1‐undecanol, while the extraction properties was almost unaffected. Moreover, it has been successfully applied to the determination of the target analytes in human urine samples, providing high extraction efficiency.